The Process of Suffering’s Cessation as Depicted in the Dependent Origination - Anh, Dang Thi Tu; Phramaha Nantakorn Piyabhani; Phramaha Somphong Khunakaro (The Journal of International Buddhist Studies College, 2024)
This research article aimed to (1) study the concept of suffering and the cause leading to suffering according to the Buddhist perspective, (2) analyze the suffering resolution based on Dependent Origination in Theravada Buddhism, (3) propose the process of suffering’s cessation as depicted in the Dependent Origination. The research methodology is documentary, involving in in-depth analysis of relevant documents and records. The findings showed that there are three, or eight, types of suffering. All suffering comes from ignorance and craving. Ignorance leads one to believe that everything is permanent and unchanging, leading to attachment and craving, which lead to clinging to existence and the cycle of rebirth. The cycle of Dependent Origination illustrates the existence of suffering and its underlying causes. To cease suffering is to eliminate the cause of suffering. The Threefold Path is a process leading to the cessation of suffering. This path, which includes training in higher virtue, higher mind, and higher wisdom, leads to the cessation of suffering, the end of ignorance, the emergence of wisdom, enlightenment, and liberation from the cycle of birth and death. When the mind is filled with precept and liberation from the cycle of birth and death. When the mind is filled with precepts, concentration naturally follows. Concentrating the mind will facilitate the contemplation of the five aggregates, leading to the emergence of wisdom, the eradication of ignorance, the achievement of enlightenment, and the cessation of suffering. This is the process of ending suffering.